Synthesis of FeAl/Al2O3 Composites by Thermite Reaction - Liu, Yin; Qian, Qian; Xu, Chuyang; Min, Fanfei; Zhang, Mingxu (Asian Journal of Chemistry, 2013)
FeAl/Al2O3 composites were synthesized by using in-situ thermite reaction of iron oxide and aluminum powder mixtures. The phase, microstructure of the composites were investigated by X-ray diffractometry, scanning electron microscopy combined with differential scanning calorimetry. The results show that a chemical rection in Fe2O3/Al system is possible and the FeAl/Al2O3 composites with the interpenetrating network structure are obtained calcined at 900 ºC for 60 min.